Sports medicine in the pediatric office : a multimedia case-based text with video - Metzl, Jordan D., 1966- (STAT!Ref electronic medical library., 2018)
Completely revised and updated, the second edition of this best-selling pediatric sports medicine resource provides step-by-step demonstrations of the examination and evaluation techniques for common sports injuries.